Effect of family doctor contract services on non-communicable disease management among the elderly: a systematic review and meta-analysis - Rong Wu; Fei Fei; Tingting Lu; Jing Zhu; Jing Zhu; Dan Hu; Dan Hu (Frontiers in Health Services)
ObjectiveThe aim of this meta-analysis was to examine the effect of family doctor contract service on managing non-communicable diseases (NCDs) among elderly patients.MethodsChinese and English articles published up to 15 July 2022 were systematically searched. Relevant randomized controlled studies (RCTs) were extracted from seven databases: PubMed, Coherence, Embase, Web of Science, CNKI, Wanfang Data, and WeiPu. All these studies have evaluated the effect of family doctor contract services on chronic disease management among the elderly. A meta-analysis was conducted using either random or fixed effects. Mean difference and risk ratio were used to analyze quantitative and qualitative data, respectively.ResultsWe identified that 25 independent studies, involving 4,046 elderly patients with chronic diseases across China, were eligible for meta-analysis. The results from these RCTs indicated that family doctors could disseminate knowledge about NCDs to elderly patients, improve their disease management abilities (including drug compliance, healthy diet, regular exercise, non-smoking, and non-drinking), lower blood pressure and blood glucose levels, reduce BMI, and increase quality of life and patient satisfaction (P < 0.05).ConclusionFamily doctor contract services could improve health management for elderly patients with NCDs and should be promoted in China.